Impact of Service Quality on Student Satisfaction: A Case Study of Public Sector Higher Secondary Institution (The Batuk, 2022)
Considering the importance of service quality, this paper aims to investigate the relationship between service quality and student satisfaction in higher education sector of Nepal. A public higher secondary school located in Panauti, was taken as the sample for the study. The descriptive and casual comparative research approaches was adopted to examine the impact of service quality on student satisfaction. A personally administered survey was administered using questionnaire based on items prescribed by  Parasuraman’s SERVQUAL (1985) and refined by Croning et al. (1992) as SERVPERF scale consisting five dimensions namely; tangibility, reliability, responsiveness, assurance, and empathy.  Over 140 students participated in the survey and 121 usable responses were received from student of the institution studying in four streams. This results of descriptive analysis indicated that students perceive relatively better provision in service quality dimensions of reliability, responsiveness, assurance and empathy than physical dimension named tangibles. In addition, the empirical result of regression analysis indicated the positive and significant influence of all five used service quality dimensions namely; tangibility, reliability and responsiveness, assurance and empathy on student satisfaction. Among these, tangibility and reliability were found strong influencers to student satisfaction.